MODELLING OF NATIONAL ECONOMIC DEVELOPMENT IN THE CONTEXT OF ENSURING SUSTAINABLE DEVELOPMENT AND HUMAN CAPITAL PROGRESS - Олена Баула; Дмитро Свинаренко; Олена Лютак; Сергій Іванцов; Андрій Жидик (Фінансово-кредитна діяльність: проблеми теорії та практики)
The sustainable development of a national economy is a central concept in modern public governance, aiming to ensure a balanced interplay between economic growth, social equity, and environmental sustainability. This study seeks to develop theoretical and methodological approaches, alongside practical tools, for modelling and forecasting sustainable economic development. Particular attention is given to the role of human capital as a critical driver that enhances labour productivity, innovation capacity, and resource efficiency. The article highlights key challenges in implementing sustainable development models: the lack of integrated modelling frameworks, insufficient and low-quality data, the pace of global change, the absence of clear methodologies, and limited innovation activity. An econometric model is constructed to evaluate the impact of sustainability components on GDP as a core macroeconomic indicator. The model incorporates economic, social, and environmental variables, emphasizing human capital as a mediating factor. Two-variable trend analyses are used to explore relationships between real GDP and selected indicators. The study identifies the most influential factors as the Consumer Price Index (%), State Budget Deficit (UAH million), Minimum Wage (UAH), Share of Renewable Energy in Total Supply (%), and Energy Consumption from Wind and Solar Sources (thousand tons of oil equivalent). Correlation and determination coefficients are calculated to quantify these relationships. GDP forecasting is conducted using logarithmic, exponential, and power regression models. Based on the findings, the paper outlines strategic directions for promoting sustainable development in Ukraine, focusing on economic, environmental, and social dimensions through the advancement of human capital. The research methodology combines a systemic and interdisciplinary approach, employing tools such as comprehensive factor analysis, strategic planning, and econometric modelling using the Data Analysis and Regression toolkit.